The effect of modification of yellow pumpkin, moringa leaves, and tamban fish in wet noodles on nutritional content and acceptability - Tinambunan, Gledis; Ardiani, Fitri (TROPHICO, 2025)
Wet noodles commonly consumed in Indonesia generally have low nutritional value, especially in protein. Their high carbohydrate content can lead to excess intake, converting into fat and causing weight gain. Therefore, innovation in noodle production is necessary to enhance nutritional value by substituting wheat flour with local ingredients such as yellow pumpkin, moringa leaves, and tamban fish. This study aims to analyze the nutritional content and acceptability of wet noodles made from these ingredients.This experimental research applies a Completely Randomized Design (CRD). The samples were wet noodles formulated with yellow pumpkin, moringa leaves, and tamban fish, evaluated by 30 panelists from the Faculty of Public Health (FKM). The Shapiro-Wilk normality test showed that the data were not normally distributed. The Kruskal-Wallis test results indicated no significant effect on color acceptability (p=0.340), a significant effect on aroma acceptability (p=0.009), a significant effect on taste acceptability (p=0.042), and no significant effect on texture acceptability (p=0.092). Based on the acceptability test and nutritional analysis, wet noodles made with yellow pumpkin and moringa leaves were preferred by panelists and had high nutritional value. The noodles contained carbohydrates (16.3%), protein (4.24%), fat (0.57%), energy (87.3 kcal), iron (15.3 mg), beta-carotene (138 mg), and calcium (154.4 mg). These findings suggest that incorporating local ingredients can improve the nutritional quality of wet noodles while maintaining consumer acceptance